2003
DOI: 10.1063/1.1587264
|View full text |Cite
|
Sign up to set email alerts
|

Emissive properties of xenon ions from a laser-produced plasma in the 100–140 Å spectral range: Atomic-physics analysis of the experimental data

Abstract: In order to design extreme ultraviolet (EUV) sources for nanolithography, xenon EUV emission has been experimentally studied in a plasma generated by the interaction of a high-power laser with a droplet jet. A theoretical model assuming that the resulting plasma is optically thick allows one to find the distribution of the relevant ions and transitions involved in the emission process. Atomic physics computations are performed using the HULLAC code to give a detailed account of the transitions involved. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 37 publications
2
80
0
2
Order By: Relevance
“…The interaction of configurations sharpens the 4d-(4f/4p) group of resonant lines. It has been shown that the interaction of configurations has a strong influence on satellite lines and reduces the width of the main 4d-4f/4p-4d broad satellite structure [42,51,53]. Therefore, interaction of all configurations has systematically been included in our HULLAC calculations leading to energy matrices including more than 3000 levels.…”
Section: Comparison Of Experimental Data Of Xe Laser-produced Plasma mentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of configurations sharpens the 4d-(4f/4p) group of resonant lines. It has been shown that the interaction of configurations has a strong influence on satellite lines and reduces the width of the main 4d-4f/4p-4d broad satellite structure [42,51,53]. Therefore, interaction of all configurations has systematically been included in our HULLAC calculations leading to energy matrices including more than 3000 levels.…”
Section: Comparison Of Experimental Data Of Xe Laser-produced Plasma mentioning
confidence: 99%
“…The configurations are selected on an energy basis [42]. For Xe 10+ whose maximum concentration is obtained around T e = 30 eV [43,51,52], all configurations with energy below 300 eV (= 10 × T e ) are kept. Above this energy, the configurations are supposed to be very little populated at moderate densities.…”
Section: Comparison Of Experimental Data Of Xe Laser-produced Plasma mentioning
confidence: 99%
“…L'élément le plus utilisé dans tout type de source est aujourd'hui le xénon. Ses caractéristiques de gaz rare en font un candidat idéal pour une source propre et son spectre présente un ensemble de transitions 4p-4d et 4d-4f non résolues [9] (UTA [10]) centrées autour de 11 nm. Cependant, son CE autour de 1% laisse supposer qu'il pourraêtre difficilement utilisé dans le futur pour des machines industrielles.…”
Section: Sources Euv : L'offreunclassified
“…We propose here a method to deal with such higher terms using detailed codes. This will allow us to check in X-ray spectra the influence of configuration interaction (CI), keeping in mind that CI was shown to be essential in EUV xenon emission analysis [11].…”
Section: Introductionmentioning
confidence: 99%